127k views
0 votes
Operations with Radical Expressions I’m still learning about this concept and I’m having trouble understanding the complexity of the problem!

Operations with Radical Expressions I’m still learning about this concept and I’m-example-1
User Happymeal
by
4.8k points

1 Answer

6 votes

Answer:

Step-by-step explanation:

Question 3.

Before we simplify the radical expression let us note the following.


\begin{gathered} 27=9*3 \\ 45=9*5 \end{gathered}

Therefore, we can write our radical function as


\begin{gathered} -\sqrt[]{27}-2\sqrt[]{27}+2\sqrt[]{45} \\ \Rightarrow-\sqrt[]{9*3}-2\sqrt[]{9*3}+2\sqrt[]{9*5} \end{gathered}

Now,


\begin{gathered} \sqrt[]{9*3}=\sqrt[]{9}*\sqrt[]{3}=3\sqrt[]{3} \\ \sqrt[]{9*5}=\sqrt[]{9}*\sqrt[]{5}=3\sqrt[]{5} \end{gathered}

therefore, our expression becomes


\begin{gathered} -\sqrt[]{9*3}-2\sqrt[]{9*3}+2\sqrt[]{9*5} \\ \Rightarrow-3\sqrt[]{3}-2(3\sqrt[]{3})+2(3\sqrt[]{5}) \end{gathered}

which simplifies to give


-3\sqrt[]{3}-6\sqrt[]{3}+6\sqrt[]{5}

since -3√3 - 6 √3 = - 9 √3 ( just add them up), the above becomes


-9\sqrt[]{3}+6\sqrt[]{5}

We cannot simplify the above function any further. Therefore, the above expression is our final answer.

Question 5.

Since -3√ 27 - 3√27 = -6 √27, our expression becomes


-3\sqrt[]{20}-6\sqrt[]{27}

Let us also note that


\begin{gathered} 20=4*5 \\ 27=3*9 \end{gathered}

therefore,


\begin{gathered} \sqrt[]{27}=\sqrt[]{3*9} \\ \sqrt[]{20}=\sqrt[]{4*5} \end{gathered}

therefore, our expression becomes


-3\sqrt[]{4*5}-6\sqrt[]{3*9}

Now since


\begin{gathered} \sqrt[]{4*5}=\sqrt[]{4}*\sqrt[]{5}=2\sqrt[]{5} \\ \sqrt[]{3*9}=\sqrt[]{3}*\sqrt[]{9}=3\sqrt[]{3} \end{gathered}

the above becomes


-3(2\sqrt[]{5})-6(3\sqrt[]{3})
\Rightarrow-6\sqrt[]{5}-18\sqrt[]{3}

We cannot simplify the above function any further. Therefore, the above expression is our final answer.

User Gorums
by
4.7k points